The Fetal Origins Hypothesis in Finance: Prenatal Environment, the Gender Gap, and Investor Behavior - Cronqvist, Henrik; Previtero, Alessandro; Siegel, Stephan; White, Roderick E. (Review of Financial Studies, 2015)
We find that differences in individuals' prenatal environments explain heterogeneity in financial decisions later in life. An exogenous increase in exposure to prenatal testosterone is associated with the masculinization of financial behavior, specifically with elevated risk taking and trading in adulthood. We also examine birth weight. Those with higher birth weight are more likely to participate in the stock market, whereas those with lower birth weight tend to prefer portfolios with higher volatility and skewness, consistent with compensatory behavior. Our results contribute to the understanding of how the prenatal environment shapes an individual's behavior in financial markets later in life. Received May 2, 2014; accepted September 30, 2015 by Editor David Hirshleifer.